Spectrally Selective Solar Absorbers based on Ta:SiO2 Cermets for Next‐Generation Concentrated Solar–Thermal Applications. Issue 7 (27th May 2020) - Bilokur, Maryna; Gentle, Angus; Arnold, Matthew D.; Cortie, Michael B.; Smith, Geoffrey B.
Abstract : An iterative algorithm is used to design a spectrally selective thin‐film stack to provide maximum solar‐to‐thermal conversion efficiency at the very high operating temperatures associated with high solar concentrations. The resulting stack is then fabricated by magnetron sputtering and characterized. It is composed of two Ta:SiO2 layers with differing Ta nanoparticle contents on a refractory metal substrate. A SiO2 antireflecting overlayer completes the stack. Optical and microstructural characterizations indicate that the stack achieves 97.6% solar absorptance up to 900 °C. Spectral selectivity and thermal stability improve on annealing in two ways, first, due to recrystallization of Pt or Ta back reflectors which lowers room temperature thermal emittance to 0.15 from 0.18, and to 0.14 from 0.21, respectively; and second, due to alloying of substrate atoms with the Ta nanoparticles of the cermet. Abstract : An iterative algorithm is used to design a spectrally selective thin‐film stack based on Ta:SiO2 cermets. The design is then fabricated by magnetron sputtering and characterized. Optical and microstructural characterizations indicate that the stack survives annealing at up to 900 °C, and still achieves 97.6% solar absorptance in this condition, with room temperature thermal emittance of 0.14.